LEADERSHIP STYLE INFLUENCE ON NURSES’ BURNOUT: A SYSTEMATIC REVIEW - Devy Syanindita Roshida; Indriati Paskarini; Tri Martiana (The Indonesian Journal of Public Health, 2023)
Introduction: We intend to evaluate the current literature, published from 2019 to 2022 and study the types of leadership styles and how they affected nurse burnout. Aims: the research was to systematically review the influence of leadership style on nurse burnout. Methods A systematic literature search was conducted through an electronic search in three databases and was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) with some inclusion criteria compiled by the research objective.  Results A total of 15 selected articles show that leadership styles affected nurse burnout both directly and indirectly. This systematic review shows that some leadership styles had an influence on increasing nurse burnout, as well as affecting their job satisfaction, psychological distress and their intention to leave. Some other leadership styles also influenced reducing nurse burnout and increasing their work engagement. Conclusions Due to the variety of leadership styles studied in the articles, it’s hard to draw specific conclusions. However, this systematic review shows most of the articles stated that some specific leadership styles took part in increasing nurse burnout, and some other leadership styles were able to reduce nurse burnout in particular.